Analisis Penerapan Media Pembelajaran Berbasis Canva Terhadap Hasil Belajar Siswa Pada Pembelajaran Tematik Di Sekolah Dasar - Nurhosen Nurhosen; Sayyinul Sayyinul; Rofik Iskandar; Malikal Balqis; Miftahus Surur (CV. Aksara Global, 2024)
The aim of this research is to determine the role of Canva-based interactive video media in thematic learning on learning outcomes in elementary schools. This research is a literature study using qualitative descriptive methods. Data collection was carried out by searching via Google Scholar for articles in electronic journals and other publications. The data was analyzed in three stages, namely organizing, synthesizing and identifying. In applying this media, several obstacles were encountered in the classroom, including; Teachers still don't know how to make designs on Canva, the signal is not stable and the infrastructure is limited. However, these obstacles are not an obstacle. The school provides socialization or training and adequate facilities and infrastructure for teachers. There are eight articles that are in accordance with the study theme which states that the application of Canva interactive media has a very significant role in student learning outcomes, especially at the elementary school level.